Enhancing hydrogen storage efficiency: Surface-modified boron nanosheets combined with IRMOF-20 for safe and selective hydrogen storage - Zabelin, D.; Tomšíková, K.; Zabelina, A.; Stastny, M.; Michalcova, A.; Mestek, S.; Burtsev, V.; Guselnikova, O.; Miliutina, E.; Kolska, Z.; Svorcik, V.; Lyutakov, O. (International journal of hydrogen energy, 2024)
The future development of human society is closely related to the development of new energy approaches which frequently will be based on green hydrogen. In this regard, one of the key research subjects is the elaboration of new materials for safe and effective hydrogen storage and transportation. In this work, we propose a hybrid hydrogen storage material based on boron nanosheets with surface-immobilized IRMOF-20. Surface immobilization was carried out in two-step procedure using covalent modification of the nanosheets surface and subsequent surface-assisted growth of IRMOF-20 from its mother liquor. Both materials (i. e. boron and IRMOF-20) have previously been reported as effective media for the hydrogen chemical sorption. However, along with a number of advantages, they have specific drawback such as low capacity or insufficient stability at higher pressure. Our main idea was to compensate the drawbacks by materials combination and enhance their effectivity in hydrogen storage. Developed materials combination exhibits high hydrogen gravimetric sorption capacity (significantly superior to boron flakes and even surpassed IRMOF-20 powder), high material stability (even at relatively high pressures) and high selectivity to hydrogen, in comparison with others, “parasitic” gases. [Display omitted] •A hybrid hydrogen storage material based on boron nanosheets with surface-immobilized IRMOF-20 was proposed.•B@IRMOF-20 combination exhibits high hydrogen gravimetric sorption capacity.•B@IRMOF-20 demonstrates relatively high stability at higher pressure.